The detailed analysis of Islamic Banking Product, Sukuk - Dr-Zia Ur Rehman; Dr-Mohammad Sohail; Liala Ilham (Journal of Religion and Society, 2025)
This article is about to understand the concept of sukuk, and its contemporary issues, implementation in the view of primary sharia resources. The objective is to explain the Islamic investment Sukuk with current terminologies in brought way, so as to provide the reader to collect the modern concept of economic and finance in Islamic structure, due to the recent banking chain, and different financial investment products are introduced. The word, financial investment, especially in Islamic law, has wide and large concept. that’s why it is a very important to understand its basic and current practices. In this research all elementary components have been presented to define the method of this concept. Financial certificates are advanced practices in the banking sector and according to the human basic need like interest-based banking system, they are trying to suppress non-interest-based banking system. In the same way insurance and other financial organizations are doing the same. likewise, bonds. According to its basic object it is based on real Islamic rules. Islamic bonds are called certificate of Islamia too. Interest and gambling are not allowed in Islamic Law. Alternatively, financial documents have introduced in the name of Sukuk. Key words: Bonds, Certificate, Sukuk, Risk, Security.